Yeast glycolipid biosurfactants. Issue 8 (12th November 2017) - Jezierska, Sylwia; Claus, Silke; Van Bogaert, Inge
Abstract : Various yeasts, both conventional and exotic ones, are known to produce compounds useful to mankind. Ethanol is the most known of these compounds, but more complex molecules such as amphiphilic biosurfactants can also be derived from eukaryotic microorganisms at an industrially and commercially relevant scale. Among them, glycolipids are the most promising, due to their attractive properties and high product titers. Many of these compounds can be considered as secondary metabolites with a specific function for the host. Hence, a dedicated biosynthetic process enables regulation and combines pathways delivering the lipidic moiety and the hydrophilic carbohydrate part of the glycolipid. In this Review, we will discuss the biosynthetic and regulatory aspects of the yeast‐derived sophorolipids, mannosylerythritol lipids, and cellobiose lipids, with special emphasis on the relation between glycolipid synthesis and the general lipid metabolism. Abstract :